DESAIN RAK TEMPAT PENYIMPANAN TABUNG GAS ARGON DENGAN KAPASITAS MAKSIMUM 3 TON: Design of the Argon Gas Storage Rack with a Maximum Load Capacity of 3 Tons - Basori; Marsudi; Aldi Hari Tri Sakti Ridwan (Universitas Negeri Jakarta, 2023)
Gas tungsten arc welding (GTAW) uses argon gas as a protective gas in the welding process. Argon gas cylinders weigh 100 kg, making it difficult to mobilize in large quantities when the welding work is at a certain height. Therefore it is necessary to create a storage area that is able to accommodate and withstand the load of gas cylinders and their contents and can be mobilized at a certain height. In order to get a suitable storage area, a design has been carried out, which includes calculating the strength of the frame, determining the material and design of the lifting lug, and calculating the welding connection of the lifting lug and hollow steel. The rack material used is SS400 type, the compressive stress that occurs due to the force acting on the hollow iron is 91.124 MPa and the stress received by the base plate is 127.5 MPa, while the allowable compressive stress for the material is 152 MPa. The load received by the lifting lug is 33,866.6 N, and the tensile stress due to the force acting on the lifting lug is 76.88 MPa, while the allowable tensile stress is 152 MPa, so the lifting lug is declared safe to use.